The Burden of and Risk Factors for Trachoma in Selected Districts of Zimbabwe: Results of 16 Population-Based Prevalence Surveys. (28th December 2018) - Phiri, Isaac; Manangazira, Portia; Macleod, Colin K.; Mduluza, Takafira; Dhobbie, Tinashe; Chaora, Shorai Grace; Chigwena, Chriswell; Katiyo, Joshua; Willis, Rebecca; Bakhtiari, Ana; Bare, Peter; Courtright, Paul; et al.
ABSTRACT: Background : Trachoma, a leading cause of blindness, is targeted for global elimination as a public health problem by 2020. In order to contribute to this goal, countries should demonstrate reduction of disease prevalence below specified thresholds, after implementation of the SAFE strategy in areas with defined endemicity. Zimbabwe had not yet generated data on trachoma endemicity and no specific interventions against trachoma have yet been implemented. Methods : Two trachoma mapping phases were successively implemented in Zimbabwe, with eight districts included in each phase, in September 2014 and October 2015. The methodology of the Global Trachoma Mapping Project was used. Results : Our teams examined 53, 211 people for trachoma in 385 sampled clusters. Of 18, 196 children aged 1–9 years examined, 1526 (8.4%) had trachomatous inflammation–follicular (TF). Trichiasis was observed in 299 (1.0%) of 29, 519 people aged ≥15 years. Of the 16 districts surveyed, 11 (69%) had TF prevalences ≥10% in 1–9-year-olds, indicative of active trachoma being a significant public health problem, requiring implementation of the A, F and E components of the SAFE strategy for at least 3 years. The total estimated trichiasis backlog across the 16 districts was 5506 people. The highest estimated trichiasis burdens were in Binga district (1211 people) and Gokwe North (854 people). Conclusion : Implementation of the SAFE strategy is needed in parts of Zimbabwe. In addition, Zimbabwe needs to conduct more baseline trachoma mapping in districts adjacent to those identified here as having a public health problem from the disease.